PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI EMPLOYEE ENGAGEMENT PADA CV. PERJUANGAN STEEL SURABAYA - jurnalpps pps; Dhian Rahma Thesiasari; Indra Prasetyo; Fatimah Riswati (Jurnal Manajerial Bisnis, 2019)
ABSTRACT Performance is the result of work that someone has achieved in carrying out work activities. High- performing employees are referred to as productive employees, whereas employees who do not reach the standards are said to be unproductive or low performing employees. The employee's ability to deliver the best results or performance for the company is strongly influenced by how he understands his job culture and strong ties with the company he works for. Employee engagement explains how much a person feels passionate and excited at working. Research conducted by CV Perjuangan Steel Surabaya find factors - factors that can affect employee performance, namely leadership, work environment, compensation and employee engagement which is the intervening variable in this study. The results obtained from this study is that the leadership variable does not affect the performance of employees in CV Perjuangan Steel, either directly or indirectly influence. Work environment and compensation variables have an influence on employee performance, either direct or indirect influence through employee engagement. Keywords: leadership, work environment, compensation, employee engagement, employee performance